RBTT-06. TESSA JOWELL BRAIN MATRIX STUDY: A BRITISH FEASIBILITY STUDY OF MOLECULAR STRATIFICATION AND TARGETED THERAPY TO OPTIMIZE THE CLINICAL MANAGEMENT OF PATIENTS WITH GLIOMA. (11th November 2019) - Watts, Colin; Apps, John; Ansorg, Olaf; Savage, Josh; Fox, Richard; Chalmers, Anthony; Short, Susan C; Thompson, Gerard; Waldman, Adam; Capper, David; Hargrave, Darren; Brennan, Paul; et al.
Abstract: In 2016 there were 5250 brain cancer deaths in the UK. Standard treatment is surgical resection followed by chemo-radiotherapy. In most cases of diffuse glioma, complete tumour resection is not feasible. Many chemotherapy drugs have untested penetration through the blood brain barrier, potentially leading to sub-therapeutic concentrations in the tumour. There is need to refine current treatment strategies in relation to the understanding of tumour biology, and rapidly introduce and evaluate novel therapeutic approaches and agents through delivering rigorous clinical trials. The TESSA JOWELL BRAIN MATRIX Study will evaluate the feasibility of delivering precision medicine for brain cancer patients within the NHS. A multicentre, platform feasibility study of 1200 patients with diffuse glioma will build on the 100, 000 genome project to develop and evaluate an infrastructure to collect and integrate: 1) real time comprehensive integrated molecular analysis, including whole genome sequencing and epigenetic classification; 2) serial sampling and annotation of tumours; 3) collection of matched clinical data; 4) assessment of patient quality of life; 5) centralised radiological review and response assessment as per RANO criteria. Once developed this will allow rapid introduction of therapeutic trials to specific patient groups. Secondary objectives include: understanding the association between extent of resection and molecular stratification to refine the role of surgery; optimisation and harmonisation of protocols to best collect, manage and store tissue, clinical data, and radiological images in order to provide a resource for researchers, both within and outside of the study. Improve patient recruitment by identifying and removing recruitment barriers and improve the information and consent processes for patients. Promote the development of a national network with expertise in brain cancer. Enrolment of the first patient is expected in late 2019. For further information, please contact the Brain Matrix Trial Office BrainMatrix@trials.bham.ac.uk.